Lack of spatial segregation in the representation of pheromones and kairomones in the mouse medial amygdala - Carvalho, Vinicius M. A.; Nakahara, Thiago S.; Cardozo, Leonardo M.; Souza, Mateus A. A.; Camargo, Antonio P.; Trintinalia, Guilherme Z.; Ferraz, Eliana; Papes, Fabio (Frontiers in Neuroscience, 2015)
The nervous system is organized to detect, internally represent and process sensory information to generate appropriate behaviors. Despite the crucial importance of odors that elicit instinctive behaviors, such as pheromones and kairomones, their neural representation remains little characterized in the mammalian brain. Here we used expression of the immediate early gene product c-Fos as a marker of neuronal activity to find that a wide range of pheromones and kairomones produces activation in the medial nucleus of the amygdala, a brain area anatomically connected with the olfactory sensory organs. We see that activity in this nucleus depends on vomeronasal organ input, and that distinct vomeronasal stimuli activate a dispersed ensemble of cells, without any apparent spatial segregation. This activity pattern does not reflect the chemical category of the stimuli, their valence or the induced behaviors. These findings will help build a complete understanding of how odor information is processed in the brain to generate instinctive behaviors.